Comparative and clinical evaluation of 1% curcumin chip versus 1% tetracycline chip as a local drug delivery agent in treating chronic localised periodontitis - a randomized control trial. - A, Chetan; Mirhajiri, Ali; Kripal, Krishna; Khan, Mahek; Farheen, Sabah (Journal of Neonatal Surgery, 2025)
Aim: To assess the efficacy of 1% Tetracycline chip and 1% Curcumin chip in management of CP patients when used as an adjunct to SRP. Materials and methods: 30 patients with CP contributing a total of 90 sites [ n = 30 each] were randomly assigned to receive one of the three treatment protocols; i.e., Group 1: SRP + 1% Tetracycline chip, Group 2: SRP + 1% Curcumin chip. Group 3: SRP alone. The following clinical parameters such as Probing Pocket Depth, Plaque Index, Gingival Index, Bleeding index were assessed at Baseline, 1 month, 3 months. Microbiological assessment was done at Baseline & 3 months. Conclusion: The results of this study suggested that local application of 1% Tetracycline chip was as effective and as beneficial as 1% Curcumin chip, in the treatment of CP patients and hence can be recommended as a treatment option for CP patients.